Anticancer Potential and Molecular Targets of Pristimerin: A Mini- Review - A. Yousef, Bashir; M. Hassan, Hozeifa; Zhang, Lu-Yong; Jiang, Zhen-Zhou (Current Cancer Drug Targets, 2017)
Pristimerin, a natural triterpenoid isolated form Celastrus and Maytenus spp, has been shown to possess a variety of biological and pharmacological effects. Recently, pristimerin has attracted more attention, especially for its potential anticancer activities. The anticancer activities of pristimerin have been illustrated in various cancer cell lines and animal models. It has been found to inhibit in vitro and in vivo proliferation, survival, angiogenesis and metastasis of tumor cells. These activities have been attributed to its modulation of various molecular targets such as cyclins, apoptosis- related proteins, proteasome activity, reactive oxygen species, as well as NF-ΚB, AKT/mTOR and MAPK/ERK pathways. This mini-review discussed the cellular impact and animal studies of pristimerin treatment, with more attention on the various molecular targets of pristimerin.
Keywords: natural compounds